The Impact of Service Quality and Corporate Image on Brand Awareness Among Tourism Businesses in Phuket Province - Subyubon, Phanat; Chaya, Phumipat; Kumboon, Amarawadee; Khiewpan, Rachapong (Journal of Liberal Arts RMUTT, 2024)
The research "The Impact of Service Quality and Corporate Image on Brand Awareness Among Tourism Businesses in Phuket Province." The aim of this research is to: 1) study the level of corporate image, service quality, and brand awareness of tourism businesses in Phuket Province; and 2) analyze the influence of corporate image, service quality, and brand awareness on the tourism business in Phuket Province. The study’s sample population consisted of 400 people from the general public who used tourism companies in Phuket province. The data analysis method comprises percentages, means, standard deviations, Pearson’s correlation, and multiple regression. The research’s conclusions showed that the corporate image of the tourism businesses in Phuket province was high overall in identity, physical characteristics, and reputation. The service quality of tourism businesses in Phuket province was considered, with the first aspect having the highest degree of empathy and the fourth having a high degree of reliability, tangibles, responsiveness, and assurance. Brand awareness of tourism businesses in Phuket Province was high in every aspect, as follows: Compare the perceptions of experience quality, perceived value, and perceived emotional benefit, in that order. The testing of hypotheses found that the corporate image affects the brand awareness of tourism businesses in Phuket Province as follows: physical characteristics(X3), identity(X1), and reputation(X2). Standardized Regression Equation is = 0.471 (X3) + 0.245 (X1) + 0.231 (X2). The service quality effect on the brand awareness of tourism businesses in Phuket Province is as follows: tangibles of the service(X1), reliability(X2), empathy(X5), responsiveness(X3), and assurance(X4). Standardized Regression Equation is Z= 0.486(X1) + 0.442(X2) + 0.234(X5) + 0.124 (X3) – 0.174(X4)